Phosphorylation of SiRAV1 at Ser31 regulates the SiCAT expression to enhance salt tolerance in Setaria italica - Qiao-lu LI; Zhi-yong LI; Meng-meng WANG; Jing-wei YAN; Lin FANG (Journal of Integrative Agriculture, 2023)
Salinity severely affects plant growth and development. Thus, it is crucial to identify the genes functioning in salt stress response and unravel the mechanism by which plants against salt stress. This study used the phosphoproteomic assay and found that 123 of the 4 000 quantitative analyzed phosphopeptides were induced by salt stress. The functional annotation of the non-redundant protein database (NR) showed 23 differentially expressed transcription factors, including a phosphopeptide covering the Serine 31 in the RAV (related to ABI3/VP1) transcription factor (named SiRAV1). SiRAV1 was located in the nucleus. Phenotypic and physiological analysis showed that overexpressing SiRAV1 in foxtail millet enhanced salt tolerance and alleviated the salt-induced increases of H2O2 accumulation, malondialdehyde (MDA) content, and percent of electrolyte leakage. Further analysis showed that SiRAV1 positively regulated SiCAT expression to modulate the catalase (CAT) activity by directly binding to the SiCAT promoter in vivo and in vitro. Moreover, we found that phosphorylation of SiRAV1 at the Ser31 site positively regulated salt tolerance in foxtail millet via enhancing its binding ability to SiCAT promoter but did not affect its subcellular localization. Overall, our results define a mechanism for SiRAV1 function in salt response where salt-triggered phosphorylation of SiRAV1 at Ser31 enhances its binding ability to SiCAT promoter, and the increased SiCAT expression contributes to salt tolerance in foxtail millet.